Correlation of Self Concept in Growing Achievement Maharah Kalam Carl Rogers Approach to MPBA Students at UIN Maulana Malik Ibrahim Malang - Jannah, Rauzatul; Machmudah, Umi; Zamziza, Muhammad Nur Farhan Bin; Zamziza, Muhammad Nur Farhan Bin; Rais, Qulyubi Mahsan Nasukha (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
الغرض من هذا البحث هو تحديد مفهوم الذات على أساس منهج كارل روجرز والعلاقة بين مفهوم الذات في تعزيز تحصيل مهارة الكلام. ويستند هذا البحث على نموذج إيجابي مع النهج الكمي، فضلا عن طريقة الارتباط. تستخدم تقنية أخذ العينات أخذ العينات الهادفة. تم جمع البيانات باستخدام عدة تقنيات، وهي؛ (أ) الاستبيان؛ (ب) الاختبار؛ و (ج) التوثيق بمقياس ترتيبي. قام الباحثون بتحليل البيانات باستخدام تحليل Chi-Square . من نتائج الأبحاث التي أجراها الباحثون، فإن مفهوم الذات له علاقة كبيرة جدًا بإنجازات مهارة كلام. يمكن أن نرى من تحليل الارتباط أن r-count = 0.027 . من جدول توزيع t مع n = 14 وباحتمال 0.05 . ثم جدول r = 0.027 . نظرًا لأن r-count > r-table ، يتم رفض Ho ويتم قبول Hi . توضح نتيجة هذا البحث أن هناك علاقة ذات دلالة إحصائية بين مفهوم الذات وتحصيل طلاب MPBA C UIN مولانا مالك إبراهيم مالانج في عام 2023 .   The purpose of this research is to determine self concept based on Carl Rogers' approach and the relationship between self concept in fostering Maharah Kalam achievement. This research is based on a positivistic paradigm with a quantitative approach, as well as a correlation method. The sampling technique uses purposive sampling. Data collection was carried out using several techniques, namely; (a) questionnaire; (b) test; and (c) documentation with an ordinal scale. The researchers analyzed the data using Chi-Square analysis. From the results of research conducted by researchers, self-concept has a very significant relationship with Maharah Kalam's achievements. It can be seen from the correlation analysis that r-count = 0.027. From the t-distribution table with n = 14 and at probability 0.05. Then r-table = 0.027. Because r-count > r-table, Ho is rejected and Hi is accepted. The conclusion of this research shows that there is a significant relationship between Self Concept and the achievement of MPBA C UIN Maulana Malik Ibrahim Malang students in 2023.